Ferroelectric control of band alignments and magnetic properties in the two-dimensional multiferroic VSe2/In2Se3. (19th October 2022) - Hu, Chen; Chen, Ju; Du, Erwei; Ju, Weiwei; An, Yipeng; Gong, Shi-Jing
Abstract: Our first-principles evidence shows that the two-dimensional (2D) multiferroic VSe2 /In2 Se3 experiences continuous change of electronic structures, i.e. with the change of the ferroelectric (FE) polarization of In2 Se3, the heterostructure can possess type-I, -II, and -III band alignments. When the FE polarization points from In2 Se3 to VSe2, the heterostructure has a type-III band alignment, and the charge transfer from In2 Se3 into VSe2 induces half-metallicity. With reversal of the FE polarization, the heterostructure enters the type-I band alignment, and the spin-polarized current is turned off. When the In2 Se3 is depolarized, the heterostructure has a type-II band alignment. In addition, influence of the FE polarization on magnetism and magnetic anisotropy energy of VSe2 was also analyzed, through which we reveal the interfacial magnetoelectric coupling effects. Our investigation about VSe2 /In2 Se3 predicts its wide applications in the fields of both 2D spintronics and multiferroics.